Parents make the difference: a randomized-controlled trial of a parenting intervention in Liberia. (4th August 2015) - Puffer, E. S.; Green, E. P.; Chase, R. M.; Sim, A. L.; Zayzay, J.; Friis, E.; Garcia-Rolland, E.; Boone, L.
Abstract : Background: The objective of this study was to evaluate the impact of a brief parenting intervention, 'Parents Make the Difference'(PMD), on parenting behaviors, quality of parent-child interactions, children's cognitive, emotional, and behavioral wellbeing, and malaria prevention behaviors in rural, post-conflict Liberia. Methods: A sample of 270 caregivers of children ages 3–7 were randomized into an immediate treatment group that received a 10-session parent training intervention or a wait-list control condition (1:1 allocation). Interviewers administered baseline and 1-month post-intervention surveys and conducted child-caregiver observations. Intent-to-treat estimates of the average treatment effects were calculated using ordinary least squares regression. This study was pre-registered at ClinicalTrials.gov (NCT01829815). Results: The program led to a 55.5% reduction in caregiver-reported use of harsh punishment practices ( p  < 0.001). The program also increased the use of positive behavior management strategies and improved caregiver–child interactions. The average caregiver in the treatment group reported a 4.4% increase in positive interactions ( p  < 0.05), while the average child of a caregiver assigned to the treatment group reported a 17.5% increase ( p  < 0.01). The program did not have a measurable impact on child wellbeing, cognitive skills, or household adoption of malaria prevention behaviors. Conclusions: PMD is a promising approach for preventing child abuse and promoting positive parent-child relationships in low-resource settings.